SOSIALISASI GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT DI DESA KUMAIN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Asiska Permata Dewi; Isna Wardaniati; Denia Pratiwi; May Valzon (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Has been done community service about dagusibu (get, use, save, and dispose) drugs correctly in Kumain Village, Rokan Hulu District, Riau. This activity is aimed to improve people's understanding in the use of drugs and is a joint effort between lecturers and the community in order to realize awareness, understanding, and community skills in using medicine properly and correctly. Minister of Health of the Republic of Indonesia on November 13, 2015 proclaimed "Movement of smart society using drugs" as part of efforts to promote, preventive and empower the community in increasing rational drug use. Community service activities will be conducted with socialization / workshop using lecture, discussion and guidance methods. The results of the devotion show that the Kumain Village community's understanding of obtaining, using, storing, and disposing of drugs is properly increased.